Characterization, Electrical Conductivity and Electrochemical Performance of Polyaniline-LiClO4-CuO Nano Composite for Energy Storage Applications. Issue 2 (22nd January 2019) - Yesappa, L; Niranjana, M; Ashokkumar, S; Vijeth, H; Raghu, S; Devendrappa, H
ABSTRACT: Polyaniline (PANI), PANI/LiClO4 composite with 5% & 10% of salt and PANI/LiClO4 /CuO NPs (PLC) nanocomposite were synthesized by chemical method and characterized them with help of fourier transform infrared spectrometer (FT-IR) spectrometer to investigate the chemical interaction between salt and confirmed the composite formation. Field emission scanning electron microscope (FESEM) is used to study the morphological changes in the composite due to effect of salt and formation of long fiber structures. provide the conducting path between the polymer matrix and the Li + ions helps to increase conductivity. The absorbance study reveals shifting of absorption wavelength towards higher end with increasing salt content in PANI is attributed to the π→π* electron transition in the benzenoid and quinoid rings. The optical band gap (Eg ) found decreasing from 2.88 to 2.35 eV for 10% of salt and 2% CuO nano NPs due to forming delocalized charges in host polymer. The dielectric parameters, and AC conductivity against frequency at different temperatures were studied. The PANI/LiClO4 composites are electrochemically stable upto 1000 th cycle with 213.08 F/g specific capacitance at 3mA/g current density for10% of salt.